Development of an information-analytical system for monitoring logistics operations of a retail network - Amosov, Hlieb; Hrama, Mykhailo (My University, 2026)
The rapid growth of the "Epicentr K" shopping center network and the expansion of its own parcel locker network require a high level of automation in logistics processes. The problem of low efficiency in monitoring locker occupancy and a significant share of manual data processing in ERP Odoo necessitates the implementation of specialized analytical solutions for operational management. Швидке зростання мережі торгових центрів «Епіцентр К» та розширення власної мережі поштоматок вимагають високого рівня автоматизації логістичних процесів. Проблема низької ефективності моніторингу заповнюваності шафок та значної частки ручної обробки даних в ERP Odoo зумовлює необхідність впровадження спеціалізованих аналітичних рішень для операційного управління.
Keywords: кафедра інформаційних технологій, штучного інтелекту і кібербезпеки; machine learning; big data; машинне навчання; великі дані